Digital literacy, fake news and education / Alfabetización digital, fake news y educación. Issue 2 (3rd April 2019) - McDougall, Julian; Brites, Maria-José; Couto, Maria-João; Lucas, Catarina
Abstract: The role of digital literacy in strengthening citizens' resilience to misinformation and 'fake news' has been the subject of research projects and networking and academic and policy discourses in recent years, given prominence by an escalation of the perceived crisis following election and referendum results in the US and UK respectively. This special issue sets out to take forward critical dialogue in the field of media and digital literacy education by publishing rigorous research on the subject. The research disseminated in this collection speaks to the political and economic contexts for 'fake news', the complex issue of trust and the risks of educational solutionism; questions of definition and policy implementation; teaching about specific subgenres such as YouTube and clickbait; international comparisons of pedagogic approaches and challenges for teachers in this changing ecosystem.